Penerapan Strategi Bercerita untuk Meningkatkan Pemahaman Akidah pada Siswa Kelas IV SDIT Masyithah Bukittinggi - Sri Yetna Juita (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
This study investigates the effectiveness of storytelling strategies in enhancing the understanding of Islamic creed (akidah) among fourth-grade students at SDIT Masyithah Bukittinggi. Employing a qualitative case study approach, data were collected through classroom observations, interviews with teachers, and documentation of learning activities. The findings reveal that systematically designed storytelling sessions significantly improved students' engagement, conceptual grasp of akidah, and positive behavioral changes, such as honesty and obedience. Challenges included time constraints and variability in student responses. Key recommendations emphasize teacher training in narrative techniques, integration of multisensory media, and collaborative partnerships with parents to sustain learning outcomes. The study underscores storytelling as an innovative pedagogical tool that bridges abstract creed concepts with students' daily experiences, fostering both cognitive and spiritual development. These results advocate for structured storytelling models in Islamic elementary education to enrich moral and religious pedagogy.